A scoping review of the healthcare provided by nurses to people experiencing domestic violence in primary health care settings - Hassan Abdulrahman H Aljomaie; Olivia Hollingdrake; Angelica Alban Cruz; Jane Currie (Elsevier, 2022)
Background: Domestic and family violence is a significant and growing public health concern in many communities around the world. Nurses are often the first and sometimes only point of contact for people seeking healthcare following DFV incidents and are therefore well placed to identify and support these vulnerable people. The aim of this scoping review is to examine the English language studies of healthcare provided by nurses in primary healthcare settings to people experiencing domestic and family violence. Methods: A scoping review of the following databases was undertaken between March-June 2021: CINAHL, Medline, and PubMed. Primary studies were included if written in English, published from 2000 onwards, and focused on the care provided by primary healthcare nurses to people experiencing DFV. A critical appraisal of included studies was conducted using the Mixed Methods Appraisal Tool (MMAT). Results were synthesised narratively. Results: Six studies were included, from the United States (n = 2), United Kingdom (n = 1), Sweden (n = 2), and Brazil (n = 1). Five studies were quantitative and one qualitative. A fundamental aspect of the healthcare provided by nurses, reported by all studies, was the screening of DFV. Other healthcare provided includes physical and mental health assessment and referral to other services, including sexual assault clinics, social supports, and law enforcement agencies. Findings suggest the level of DFV screening conducted by nurses is limited. Nurses' knowledge of how to support people experiencing DFV was also reportedly limited. Two studies reported that nurses were unfamiliar with DFV practice guidelines and the existence and availability of support networks for people experiencing DFV. Conclusion: Findings suggest inconsistency in primary healthcare nurses' level of education, skill and knowledge, and detection of people experiencing DFV. As the largest healthcare professional discipline, nurses have frequent contact with people experiencing DFV. There is an urgent need for nurses to be better educationally prepared and more organisationally supported in order to adequately respond and provide healthcare to people experiencing DFV. Given that the number of people experiencing DFV has increased due to the COVID-19 pandemic, it is ever more important for nurses to be well equipped to identify and respond appropriately.